Emerging Equity Markets : Growth, Benefits, and Policy Concerns - Kumar, Manmohan (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1994)
Since the mid-1980s, there has been a very substantial increase in stock market activity in many developing countries. This paper first examines the main characteristics of the emerging stock markets, and illustrates the evolution of equity prices in these markets over the last decade. It then discusses the reasons for the markets' growth and assesses the extent to which domestic policies, as well as external factors, have played a role. This is followed by a discussion of the likely benefits of these markets; the effects which any abrupt correction in stock prices could have for the economy; and the ways in which these markets can be made more efficient.